2017
DOI: 10.2174/1874325001711010239
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Management of Radial Head and Olecranon Fractures

Abstract: Background:Advancement in surgical techniques and implants has improved the ability to manage radial head and olecranon fractures. However, trends in management of these fractures are largely unstudied.Objective:This purpose of this study is to evaluate management trends for these common fractures.Methods:A retrospective review of a comprehensive Humana database was performed using Pearl Diver supercomputer (Warsaw, IN, USA) for radial head and neck (RHNF) and olecranon fractures (OF) between 2007 and 2014. Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…Our study has achieved a similar result with the few other studies available in the literature [19,[23][24][25][26]. This study has notably reported good to excellent results with adequate multi-dimensional surgical treatment.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our study has achieved a similar result with the few other studies available in the literature [19,[23][24][25][26]. This study has notably reported good to excellent results with adequate multi-dimensional surgical treatment.…”
Section: Discussionsupporting
confidence: 88%
“…Algorithms for unstable elbow injuries were created to simplify the flow of operative decision making.We followed it for all the patients included in the study and achieved good results according to the MEPS. Compared with other similar studies, the strength of this paper is that there were no poor results amongst our cohorts [19][20][21][22].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…To increase elbow stability and perform early functional exercises for patients with terrible triad of the elbow, some scholars advocate the combined use of a hinged external fixator. Motisi et al [ 16 ] found that a hinged external fixator effectively maintained elbow stability, prevented elbow dislocation, and achieved a satisfactory clinical effect in 35 patients with terrible triad of the elbow.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the decision to either fix or replace the radial head remains controversial. There has, however, been a recent trend observed towards an increase in the use of REP in radial head fractures, as arthroplasty provides early stability and may allow mobilisation sooner, potentially resulting in a better functional outcome [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%